Regulatory impact assessment of the implementation of the IPPC directive to the pig industry in England and Wales. - Pellini, Tiago (Cranfield University, 2002)
The Directive 96/61/EC on Integrated Pollution Prevention and Control (IPPC) is an important element of the EU strategy of sustainable development. IPPC imposes environmental regulation upon industries considered to have high potential for pollution, including the intensive rearing of pigs. Having its origins in the environmental regulation of the manufacturing and processing industries, the application of IPPC to the agricultural sector justifies particular attention and support. The required use of Best Available Techniques (BAT) offers a particular challenge to the sector. This thesis develops and applies a framework for the assessment of the impact of IPPC on the pig industry in England and Wales. Three case study pig installations are used to compare changes in performance between `without' and `with' IPPC situations. Particular attention is paid to the impact of IPPC on capital and operating costs, and on commercial viability. This is set against the environmental benefits obtained. The validity of the predictions based on the case studies for the pig industry as a whole are assessed by means of a sectoral postal survey of pig producers and a workshop with key stakeholders. The case study analysis confirmed that design and operation of animal housing and waste management systems are the most critical factors for IPPC introduction. Significant environmental improvements are possible by applying BAT to pig installations, especially through the reduction of ammonia emissions. Estimated abatement costs ranged between £3 and £6 per kg of ammonia abated. The total compliance costs for existing installations were substantial, at levels unlikely to be absorbed by the margins, but compliance with IPPC is expected to have a relatively lower financial impact for new installations. There is a risk that the current approach to BAT may not ensure a completely integrated approach to environmental protection. Notwithstanding this, the IPPC regime represents a significant step towards the internalisation of externalities caused by intensive pig production. IPPC is likely to reinforce and guide the structural change and technological innovation in this sector to more efficient and environmentally responsible production systems.
Keywords: Pollution; pigs; industry; IPPC; animal housing; waste management; ammonia emissions